HUBUNGAN MANAJEMEN KELAS DENGAN PENERAPAN PENDIDIKAN KARAKTER DALAM KURIKULUM 2013 JURUSAN OTOMOTIF SMK NEGERI 3 JAYAPURA - FEBI ADRIANA MUTIARA SOGALREY; DIKI KURNIAWAN; ABDUL KARIM (Universitas Cenderawasih, 2020)
This study aims to look at the correlation between classroom management and the application of character education in Kurikulum 2013 in the Automotive Department, SMK Negeri 3 Jayapura. This research was a quantitative study, with a sample of 173 people from 314 populations. Methods of data collection were using questionnaires / questionnaires and observations, through validity and reliability testing using product moment correlation and calculations assisted with Statistical Package for Socience version 25 (SPSS). From the results of the study showed that there was a positive relationship between classroom management and the application of character education in Kurikulum 2013, seen from the results of a correlation of 0.730 with a comparison of rcount> rtable (0.730> 0.148). In addition, the relationship between classroom management and the implementation of character education in Kurikulum 2013 is 73% and the remaining 27% was determined by other factors, such as character education in the family and society because the factors for successful implementation of character education in Kurikulum 2013 come from families, schools and public. Keywords: Class Management, Character Education, Curiculum